2020
DOI: 10.3390/agronomy10050670
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Drought Stress and Soil Cultivation in Chardonnay and Xynisteri Grape Cultivars

Abstract: Cyprus has a long tradition in grape cultivation and wine making and grapevine is important for the sustainability of the agricultural sector, like in other Mediterranean areas. Water scarcity, which is projected to increase due to climate change, could negatively affect the sector. In this research, the effects of irrigation and tillage treatments on various aspects of vine growth and product quality (e.g., yield, physiology and quality attributes), were studied in Chardonnay and Xynisteri cultivars grown in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 56 publications
(76 reference statements)
1
16
0
Order By: Relevance
“…For the main viticulture regions of the world, a decrease in rainfall and an increase in high temperatures (Biasi et al, 2019;Santos et al, 2020) become risk factors and enhance the need for irrigation (Hall et al, 2016;Chrysargyris et al, 2020). The HTC decrease throughout ER is limiting non-irrigated viticulture to the north of the Caspian Sea, where climate aridity will grow.…”
Section: Discussionmentioning
confidence: 99%
“…For the main viticulture regions of the world, a decrease in rainfall and an increase in high temperatures (Biasi et al, 2019;Santos et al, 2020) become risk factors and enhance the need for irrigation (Hall et al, 2016;Chrysargyris et al, 2020). The HTC decrease throughout ER is limiting non-irrigated viticulture to the north of the Caspian Sea, where climate aridity will grow.…”
Section: Discussionmentioning
confidence: 99%
“…However, deficit irrigation might not be sufficient for introduced cultivars. For Chardonnay, irrigation is required for high yield and adequate grape quality in the Cypriot climate [ 90 ]. Because of the changing climate, it is increasingly important to choose plants that are well-suited to their planting location to minimize additional inputs.…”
Section: Discussionmentioning
confidence: 99%
“…They studied M4 rootstocks and concluded that carbon metabolism, mitochondrial function and other as yet unidentified mechanisms may be involved in the root mass, drought tolerance effect in grapevines. Chrysargyris et al, (2020) in their study comparing Xynisteri to Chardonnay found that non-irrigated…”
Section: Potted Vine Trialsmentioning
confidence: 99%
“…They however identified that in a vineyard, Maratheftiko had higher chlorophyll content than Xynisteri, which was not the case with the potted trials. Chrysargyris et al, (2020) compared Xynisteri with Chardonnay in a vineyard and found that the level of chlorophyll amongst irrigation and no irrigation groups varied. In irrigated vines, chlorophyll decreased at flowering and increased at veraison with no irrigation.…”
Section: Potted Vine Trialsmentioning
confidence: 99%
See 1 more Smart Citation